2013
DOI: 10.1016/j.jcf.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antibiotic treatment for pulmonary exacerbations on bacterial diversity in cystic fibrosis

Abstract: Antibiotic treatment directed at P. aeruginosa has an additional significant impact on non-pseudomonal, co-colonising species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 28 publications
6
51
1
Order By: Relevance
“…time of exacerbation but before the administration of antibiotic therapy, which may have a significant impact on bacterial community structure (5,13).…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…time of exacerbation but before the administration of antibiotic therapy, which may have a significant impact on bacterial community structure (5,13).…”
Section: Original Researchmentioning
confidence: 99%
“…More specifically, it is not known whether significant changes in airway bacterial communities occur around the time of pulmonary exacerbations, events that are well known to be associated with a progressive and irreversible decline in lung function, increased hospitalization and antibiotic use, decreased quality of life, and increased mortality rates (7)(8)(9)(10)(11)(12). Studies addressing this important question have provided valuable insight but have been limited by cross-sectional design, small numbers of paired baseline-exacerbation samples from the same individual, and a focus on relatively narrow measures of bacterial community change (e.g., total bacterial density or community diversity) (5,6,(13)(14)(15).…”
mentioning
confidence: 99%
“…Our goal was to deter- mine if a bacteria-derived biomarker can be identified and result in antibiotic treatment being initiated early in the course of a PE and reduce the symptoms that would otherwise cause damage to the lungs. Identifying a change in microbiota that precedes a PE requires frequent patient sampling, since the length of time between the changes in the bacterial community and PE onset is unknown (14). Previous cross-sectional studies examining the diversity of the microbiota in the lungs of CF patients collected samples at a frequency or for a length of time that did not reveal potential short-term changes associated with a PE (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…(12) used quantitative PCR (qPCR) on bacterial DNA isolated from sputum samples collected weekly over a 12-month period to identify the cause of PEs in 12 CF patients. Using this quantitative analysis, Stressman et al (12) showed that the bacterial load, including the dominant pathogen, P. aeruginosa, did not change 1 to 3 weeks prior to the onset of a PE.Because a single sputum sample can provide only a snapshot of the community profile at any given time, the identification of changes in the microbiota that precede PE onset would require frequent longitudinal sampling (13,14). Our long-term study was designed to determine if combining quantitative and deep-sequencing techniques with intensive sampling from a single patient over a time period of years would reveal population changes, undetected in previous studies, prior to the onset of antibiotic treatment or a PE.…”
mentioning
confidence: 99%
See 1 more Smart Citation